A proposal to develop the performance of the administrative staff at Hail University using the performance management portal - Abu Hegazy, Samir Rabie El-Sayed; Mahmoud, Ahmed Issa; Al-Alfi, Hani Rizk Abdel-Gawad; Al-Mutairi, Abdulaziz bin Abdul Hamid (Journal of Educational and Psychological Sciences, 2020)
The study aimed to develop a proposed scenario for the development of the performance of the administrative staff at Hail University using the performance management approach. The study used the descriptive method. The tool consisted of a questionnaire distributed to a sample of 300 managers. The first axis of the tool was (3.56) with a high grade. The first axis achieved the psychological security of the employees; the average was 3.49 with the grade (large) The internal work environment scale averaged 2.88 (average). , And reached a proposed vision in the form of a set of measures to be implemented on the ground, and the study recommended the need to develop programs for the continuous development of the performance of administrators.
Keywords: Suggested perception; performance; administrative apparatus; University of Hail; performance management